SOIL PHOSPHORUS AVAILABYLITY EVALUATION FOR CORN BY MEHLICH-1 AND MEHLICH-3 SOIL TEST METHODS - BORTOLON, Leandro; GIANELLO, Clesio; SCHLINDWEIN, Jairo André (Scientia Agraria, 2009)
Phosphorus is the most plant’s nutrients that have been studied for soil test methodologies, due the dynamic complexity of soil phosphorus resulting in a wide range soil test methods. The Mehlich-1 solution have been used by soil testing laboratories for several years, however this solution overestimate the soil phosphorus availability for plants in soils under recently rock phosphate amendment. The Mehlich-3 solution was proposed for acid soils and soils that received rock phosphate. This study was carried out to compare the Mehlich-1 and Mehlich-3 solutions to evaluate soil phosphorus availability for corn in six soils of the Rio Grande do Sul state. The determination coefficients obtained among corn phosphorus absorbed and soil phosphorus were: 0.88 for Mehlich-1 and 0.91 for Mehlich-3 solutions. The soil phosphorus amounts extracted by solutions have been high association degree (r = 0.99). The soil phosphorus amounts extracted by solutions have been high relation degree among the corn absorbed phosphorus amounts and corn dry matter shoot; the solutions did not differed among the soil phosphorus and corn absorbed phosphorus. The solutions are efficient to evaluate the soil phosphorus availability for corn.